Arthroscopic Double-Row Bony Bankart Bridge Repair Using a Tensionable Knotless System - Liles, Jordan (Arthrosc Tech, 2021)
Posterior labral pathology is common in contact athletes; however, posterior glenoid avulsion fractures, also known as posterior bony Bankart lesions, are less common. Posterior instability affects approximately 10% of all patients with shoulder instability. Diagnosis in these high-risk individuals often follows a traumatic posterior dislocation. The patient feels grossly unstable but may or may not have recurrent dislocations beyond the initial trauma. Surgical correction and favorable surgical outcomes require a full understanding of both the soft-tissue and bony components of the injury. Stable osseous fixation is required to restore appropriate glenoid version, depth, and to prevent malunion. We present a technique to mobilize and stabilize a posterior bony Bankart lesion with a knotless suture bridge construct. We feel that this technique is reliable and reproducible and allows for a superior quality of fragment reduction when compared with systems using larger anchors and knotted systems.